Peningkatan Keterampilan Menulis Siswa Menggunakan Media Koran Bergambar - Natasya Dela Puspita; Dita Nur Pangestu; Wahyu Purwasih; Siti Sarah (Jurnal Sekolah Dasar, 2023)
Efforts to Improve Students' Writing Skills Through Illustrated Newspapers for Grade 5 SDN 1 Metenggeng. Grade 5 students at SDN 1 Metenggeng, this study aims to improve writing skills. The research method used is classroom action research (PTK) with various models. This can be seen from the results of the class action with Kurt Lewin's PTK model, students enthusiastically followed the instructions when the class action was carried out through the use of illustrated newspapers. In addition, before carrying out the lesson, take advantage of comic book media for lesson plans for class 5 topic 2 (clean air for health). This allows students to develop their narrative writing skills. The results of the research show that to draw conclusions by analyzing the characteristics through the main idea of ​​a text in a structured and what it is.